2008
DOI: 10.1007/s00392-008-0681-6
|View full text |Cite
|
Sign up to set email alerts
|

Bisoprolol vs. carvedilol in elderly patients with heart failure: rationale and design of the CIBIS-ELD trial

Abstract: This is the first large scale head to head beta-blockers trial in an elderly population with CHF. Besides determining which of two standard beta-blockers is best tolerated in elderly patients with systolic or diastolic CHF, we expect to gain further insight into the treatment of the particular population of patients with diastolic CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 29 publications
1
27
1
1
Order By: Relevance
“…24 Bristow et al also reported that carvedilol produces dose-related improvements in HF patients, 4 whereas a study by Dungen et al showed that the potency of carvedilol at a target dose of 50 mg per day and bisoprolol at 10 mg per day is approximately equal. 25 Second, the dosages of the 2 β-blockers in our study were lower than the common dosages found in the many large-scale trials. Asanuma et al reported that carvedilol suppressed the frequency of ventricular fibrillation and death through reducing infarct size after ischemia reperfusion injury.…”
Section: Konishi M Et Alcontrasting
confidence: 59%
“…24 Bristow et al also reported that carvedilol produces dose-related improvements in HF patients, 4 whereas a study by Dungen et al showed that the potency of carvedilol at a target dose of 50 mg per day and bisoprolol at 10 mg per day is approximately equal. 25 Second, the dosages of the 2 β-blockers in our study were lower than the common dosages found in the many large-scale trials. Asanuma et al reported that carvedilol suppressed the frequency of ventricular fibrillation and death through reducing infarct size after ischemia reperfusion injury.…”
Section: Konishi M Et Alcontrasting
confidence: 59%
“…As this is frequently not possible, even in a cardiology setting [32], specialized ambulatory settings should be developed [24,33]. Whether this is feasible in an ever-aging and fragile population with CHF is an unresolved issue, but the recently completed Cardiac Insufficiency Bisoprolol Study in the Elderly (CIBIS-ELD) trial [34] should provide the missing link for our clinical practice.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 97%
“…BB was up-titrated toward the target dose in Japan [10] (carvedilol 20 mg/day, bisoprolol 5 mg/ day), and the up-titration was halted in the following circumstances: worsened HF status including peripheral hypoperfusion, systolic blood pressure of <90 mmHg, heart rate (HR) of <60 beats/min, eruption of grade II or III atrioventricular block, and subjective symptoms such as dizziness. Daily doses of BB were demonstrated as equivalents of carvedilol (carvedilol-equivalent doses: metoprolol, 2; bisoprolol, 0.2) [11][12][13].…”
Section: Subjects and Clinical Measurementsmentioning
confidence: 99%